Euro Zone Crisis vsersus Poland (Economic and Political Thought, 2012)
The actual crisis in the euro zone results from the inconsistent attitude ofthe members of the region towards the demands of the economic integrationprocess. Its extension towards the creation of an effectively functioningfinancial and economic union is immanently connected with the need ofa bigger and bigger convergence of the economic policy adopted by theparticipants of the integration actions, especially in the context of their fiscaland budgetary policy. The lack of political will that made full implementationof such a project possible together with a voluntary policy of accessing theeuro zone by the states that did not meet the necessary requirements andcriteria neither at the moment of accession nor later, and negligence in theirexecution led to a deep crisis in the zone as well as the whole EuropeanUnion. The proposed methods of reforming the situation result from theinterests of the two European integration ‘engines’: Germany and France,and they do not create conditions necessary for finding a final solution tothe existing problems.On the other hand, Poland’s attitude towards the euro zone crisisis determined by the state and perspectives of our economy, the qualityof the domestic political elite and the manner of economic management.Confrontation with the problems of the euro zone crisis in the context ofaccession is strictly determined by the ability to implement necessary reformsin order to create economic conditions adequate to challenges.